Evolutionary trajectory of phytoalexin biosynthetic gene clusters in rice. (8th July 2016) - Miyamoto, Koji; Fujita, Masahiro; Shenton, Matthew R.; Akashi, Shota; Sugawara, Chizu; Sakai, Arisa; Horie, Kiyotaka; Hasegawa, Morifumi; Kawaide, Hiroshi; Mitsuhashi, Wataru; Nojiri, Hideaki; Yamane, Hisakazu; et al.
Significance Statement: In plants, pathways for specialized metabolites are sometimes encoded by operon‐like gene clusters. Here were use comparative genomics and biochemical studies in rice species to provide an evolutionary insight the mechanisms of formation of gene clusters encoding diterpene phytoalexins. Summary: Plants frequently possess operon‐like gene clusters for specialized metabolism. Cultivated rice, Oryza sativa, produces antimicrobial diterpene phytoalexins represented by phytocassanes and momilactones, and the majority of their biosynthetic genes are clustered on chromosomes 2 and 4, respectively. These labdane‐related diterpene phytoalexins are biosynthesized from geranylgeranyl diphosphate via ent ‐copalyl diphosphate or syn ‐copalyl diphosphate. The two gene clusters consist of genes encoding diterpene synthases and chemical‐modification enzymes including P450s. In contrast, genes for the biosynthesis of gibberellins, which are labdane‐related phytohormones, are scattered throughout the rice genome similar to other plant genomes. The mechanism of operon‐like gene cluster formation remains undefined despite previous studies in other plant species. Here we show an evolutionary insight into the rice gene clusters by a comparison with wild Oryza species. Comparative genomics and biochemical studies using wild rice species from the AA genome lineage, including Oryza barthii, Oryza glumaepatula, Oryza meridionalis and the progenitor of Asian cultivated rice Oryza rufipogon indicate that gene clustering for biosynthesis of momilactones and phytocassanes had already been accomplished before the domestication of rice. Similar studies using the species Oryza punctata from the BB genome lineage, the distant FF genome lineage species Oryza brachyantha and an outgroup species Leersia perrieri suggest that the phytocassane biosynthetic gene cluster was present in the common ancestor of the Oryza species despite the different locations, directions and numbers of their member genes. However, the momilactone biosynthetic gene cluster evolved within Oryza before the divergence of the BB genome via assembly of ancestral genes.